1998
DOI: 10.1046/j.1365-2141.1998.01066.x
|View full text |Cite|
|
Sign up to set email alerts
|

Primordial role of CD34+38 cells in early and late trilineage haemopoietic engraftment after autologous blood cell transplantation

Abstract: Summary. In order to better define which cell subset contained in graft products might be the most predictive of haemopoietic recovery following autologous blood cell transplantation (ABCT), the relationships between the amounts of reinfused mononuclear cells (MNC), CFU-GM, total CD34 þ cells and their CD33 and CD38 subsets, and the successive stages of trilineage engraftment kinetics, were studied in 45 cancer patients, using the Spearman correlation test, a linear regression model and a log-inverse model. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 36 publications
(51 reference statements)
5
33
0
Order By: Relevance
“…These findings are consistent with those of Henon et al (1998), including the suggested threshold dose of 0·05 × 10 6 /kg CD34 þ CD38 ¹ cells for rapid engraftment: 4/4 patients transplanted with at least this dose achieved rapid neutrophil engraftment (< 11 d), compared to only 4/10 patients transplanted with less than this. Several authors have subdivided the CD34 þ CD38 ¹ population on the basis of HLA-DR expression (Huang & Terstappen, 1994;Rusten et al, 1994).…”
Section: ¹0·683 Psupporting
confidence: 80%
See 2 more Smart Citations
“…These findings are consistent with those of Henon et al (1998), including the suggested threshold dose of 0·05 × 10 6 /kg CD34 þ CD38 ¹ cells for rapid engraftment: 4/4 patients transplanted with at least this dose achieved rapid neutrophil engraftment (< 11 d), compared to only 4/10 patients transplanted with less than this. Several authors have subdivided the CD34 þ CD38 ¹ population on the basis of HLA-DR expression (Huang & Terstappen, 1994;Rusten et al, 1994).…”
Section: ¹0·683 Psupporting
confidence: 80%
“…From these new experiments we believe that a false positive reaction for CD7 can be excluded in our previous data by our routine flowcytometric analysis. Henon et al (1998) described the role of CD34 þ CD38 ¹ cells in early and late trilineage engraftment after PBSC transplantation, and identified better correlation with haemopoietic recovery of CD34 þ CD38 ¹ than total CD34 þ cells. We report similar findings in a group of patients undergoing peripheral blood stem cell (PBSC) transplantation in Belfast City Hospital, Belfast, Northern Ireland, and in addition include analysis of the relationship with post-transplant recovery of the CD34 þ CD38 ¹ HLA-DR ¹ population.…”
Section: Department Of Haematologymentioning
confidence: 99%
See 1 more Smart Citation
“…Eligible patients had histologically confirmed CD20+ B-cell lymphomas (according to the World Health Organization classification) in progressive disease or partial remission after at least one line of treatment. Patients had to be at least 18 years old, have lesions measurable on 18 FDG-PET/CT, World Health Organization performance status ≤ 2, absolute neutrophil count (ANC) ≥ 1500/μl, platelet count ≥ 100.000/μl and a life expectancy of at least 6 months.…”
Section: Patient Selectionmentioning
confidence: 99%
“…14,15 Here, the correlation of cell dose with engraftment kinetics appears to be even more pronounced when considering the CD34 ϩ CD38 Ϫ subset. 16 There are fewer studies that analyze the effects of growth factor use, CD34 ϩ dose or other patient or donor characteristics on engraftment kinetics in recipients of T celldepleted (TCD) marrow grafts. However, it would appear that neutrophil engraftment is accelerated with growth factor treatment in this setting as well.…”
mentioning
confidence: 99%